Relative to what? Cross-national picture of European poverty measured by regional, national and European standards - Olli Kangas; Veli-Matti Ritakallio (Luxembourg Income Study (LIS), 2004)
The starting point in the paper is the relative concept of poverty. We will study how our picture of poverty will change if we accept a very relative concept of poverty. The first problem we encountered was the selection of the benchmark. A couple of alternative ways to conduct relativizations were selected. First, we applied the conventional poverty approach. The poor were those whose income remained below 60% of the national equivalent disposable income. Second, we collapsed European nations together into one data pool and calculated a common poverty line for the EU. This EU line was then applied in subsequent analyses. Thirdly, we decomposed nation states into smaller units representing the poorest and richest areas in respective countries. Data were compiled from the Luxembourg Income Study. If we apply the conventional nation-based ways of operationalizing poverty (poverty line 60% of median income) the poverty rate varies from 7,1% in Sweden to 20,5% in Italy. The shift to the common European poverty line will expand that gap. The variation is from 0,7% in Luxembourg to 43,1% in Spain. Numerically and methodologically the most interesting issues are revealed when we compare regional, national and EU level relativizations. Our exercise indicates that within-nation differences are sometimes more pronounced than differences between nations. Therefore, very often national means tend to obscure more than they reveal. The seriousness of the problem varies between groups of countries. In the egalitarian Nordic countries incomes between regions as well as between individuals are more evenly distributed and consequently, the national means are more representative for these countries. Moreover, the Scandinavian cluster is more or less robust against the mode of comparison. The low poverty rates in the Nordic countries do not essentially change even if we change from national to regional or cross-national poverty lines. The change in the method of relativization does not alter our understanding of Scandinavian poverty but it has a substantial impact upon our picture of the Mediterranean countries. The use of the European poverty line leads to two to three times higher poverty rates than analyses based on purely national data. Also, the regional variation in these countries is the widest. Therefore, conclusions based on national means may in some cases be severely misleading. The results also have some bearing for our use of purchasing power parities. In societies with large socio-economic and regional variation in income, and consequently in consumption capacities, purchasing power parities implicitly assuming homogenous consumption patterns over society may give a distorted picture of the price levels in a country in question. When it comes to the Central European countries, to some extent the same story as was told in the Scandinavian case is valid. The countries are not that sensitive to changes in the calibration of the measurement instruments. Also the results for the UK are pretty robust but the main difference between the UK and Central-Europe is that the poverty rate is about 10 percentage points higher in the former.
Keywords: 330; Armut; Einkommensverteilung; Regionale Disparität; Messung; EU-Staaten